Glyphosate in availability of manganese in soils (Research, Society and Development, 2021)
Glyphosate is widely used in the world due to its wide efficiency in weed control. Because it has chelating properties, herbicide can form complexes with cations, interfering in absorption of nutrients by plants. Thus, the aim was to evaluate the availability of manganese (Mn) under different doses of glyphosate in a sample without soil, in a Entisol and in a Oxisol. Collected in Sinop - Mato Grosso. For this, a batch assay was performed to evaluate the influence of different doses of glyphosate on the Mn sorption. The glyphosate doses evaluated were: 0; 2.5; 12.5; 50 and 125 L ha-1. The doses of Mn were: 0; 15.8; 27.8; 43.2 and 57.1 mg L-1. Both prepared in CaCl2 at 0.01 mol L-1. The experimental design was in completely randomized design, with three replications per treatment. The results were subjected to analysis of variance, and when significant, analyzed by the Scott Knott test at 5% probability. Freundlich's isotherm was better adapted to the data. The parameters Kf and n did not differ among treatments. Greater sorption of Mn was observed in the Oxisol compared to the Entisol. In 15.8 mg L-1 of Mn, higher doses of glyphosate resulted in less Mn available in the solution of the two soils analyzed. However, in the other Mn concentrations, the increasing doses of glyphosate resulted in more Mn available in the solution. Glyphosate was able to complex Mn in the recommended dose of micronutrient for both soils.